Correlation between Slope 2 in Clot Waveform Analysis of Activated Partial Thromboplastin Time with Factor VIII Activity in Hemophilia A - Raissa Yolanda; Delita Prihatni; Coriejati Rita; Dewi Kartika Turbawaty (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Hemophilia A is an inherited factor VIII deficiency disease, related to X chromosome. Diagnosis of Hemophilia A is made based on Factor VIII assay. Nowadays, Hemophilia A therapy is by giving factor VIII concentrate, so that monitoring of this therapy must be done by examine Factor VIII activity, but examination of Factor VIII activity is currently still limited in facilities and quite expensive. One of activated partial thromboplastin time (aPTT) optical methods can provide information about every stage of coagulation through clot waveform analysis. Factor VIII activity can describe in slope 2 of clot waveform analysis, which deficiency of factor VIII will cause slope 2 slighter than normal, because the clot form is not optimal and the light transmission recorded at clot waves do not decrease maximally. The aim of this study was to analyze the correlation between slope 2 on the clot waveform analysis of the optical method on aPTT test with Factor VIII activity in hemophilia A subjects. This was a correlative observational study cross sectional study, conducted at Hasan Sadikin General Hospital Bandung in August 2018-September 2019. The subjects were member of Hemophilia A sufferers of West Java Hemophilia Society. The research subjects were assesed for Factor VIII activity and optical method of aPTT. Slope 2 calculated from the clot waveform analysis that formed in aPTT examination. This study involved 43 subjects, with a median age of 6 years, an age range of 1-45 years, and 51.2% of patients aged 6-17 years. The results of Factor VIII activity in this study had a median 0% with a range 0-25.9%, and the value of slope 2 had a median 1.0%T/sec with a range 0.5-3.5%T/sec. The correlation test between slope 2 and Factor VIII activity with 95% confidence interval using Spearman's correlation test showed very strong positive correlation which statistically significant (r = 0.854 and p <0.001). Conclusion: there was a statistically significant very strong positive correlation between slope 2 on the clot waveform analysis of aPTT optical method test with the activity of Factor VIII in Hemophilia A.